The Role of Physical Education in Forming Students' Character Education (Systematic Literature Review) - Siti K S, Aulia Yasmin; Adh Dhuha, Zahra Ulwani; Aimar, Dida; Saputra, Dewan Agung; Maulana Rifki, Muhamad Taufik; Nurfaidah, Tria; Rizkyanfi, Mochamad Whilky (Jurnal Ilmiah Mandala Education (JIME), 2024)
The purpose of this systematic literary study is to study scientific literature on the role of physical education in the formation of student character education. This research uses the Google Scholar website and Harzing’s Publish or Perish app to search for database articles, especially on Google Scholars over the past 5 years, to select articles that contain information about the role of physical education in shaping student character education. To perform journal searches, we used methods of systematic literature review, which continued with the process of filtering and data extraction using the flowchart PRISMA (Preferred Reporting Items for Systematic Review and Meta-Analyses) to identify articles. Of the 400 articles downloaded, 10 final articles pass the process of filtering inclusion and exclusion based on criteria that are defined and will be analyzed. The results of the review of the article conclude that physical education has an important role in the formation of the character of pupils at all levels of education. Studies have shown that physical education contributes to the development of character values such as responsibility, discipline, enthusiasm, honesty, cooperation, and other social values.